Domesticity and political participation: At home with the Jacobin women - Berges, Sandrine (Political Research Quarterly)
The exclusion of women from political participation and the separation of private and public spheres seem anchored in human history to such an extent that we may think they are necessary. I offer an analysis of a philosophical moment in history, the early years of the French Revolution, where politics and domesticity were not incompatible. I show how this enabled women to participate in politics from within their homes, at the same time fulfilling their duties as wives and mothers. The republican home, on this interpretation, was a place of power and virtue, a merging of the public and the private sphere where political ideals and reforms could be born and nurtured. This conception of the home was derived in great part from a reading of Rousseau$1 (Bs writings on motherhood. As the influence of French revolutionary women became more visible, they were severely repressed. The fact that they could not hold on to a position of power that derived naturally from the ideals they and others defended, I will suggest, was caused both by the fact that the framework used to allow women political power was insecure, and by the gradual replacement of republican ideals by liberal ones.s
Keywords: Political participation, Gender, Domesticity, Public and private sphere, French revolution, Feminism